ASVAC2022 : 8th Asian Vaccine Conference - Geethani C. S. Galagoda; Jennifer Perera; Rajiva de Silva; H. T. Wickramasinghe; Dhanushka Dasanayake; Lulu Bravo; Zulkifli Ismail; Daniel Y. T. Goh; E. Anthony S. Nelson (Taylor & Francis Group, 2023)
Aiming to further the Immunization Partners in Asia Pacific (IPAP)'s vision of a world where no one suffers from a vaccine preventable disease, the 8th Asian Vaccine Conference (ASVAC 2022) was held in Colombo, Sri Lanka and virtually from 15 to 18, September 2022 (www.asianvaccine.com). This conference followed those held in Siem Reap, Cambodia (2009), Manila, Philippines (2010), Jakarta, Indonesia (2011), Cebu, Philippines (2013), Hanoi, Vietnam (2015), Singapore (2017) and Naypyidaw and Yangon, Myanmar (2019). The ASVAC2022 themed "Immunization: in Era of Pandemics," commenced with the EPI Managers' Workshop, followed by pre-conference workshops and Vaccinology Masterclass, followed by the main conference featuring 5 plenary lectures, 6 partner-led symposia, free paper and poster presentations, and industry-supported lunch and evening sessions. There were over 1830 registered participants, with 112 attending in person and 998 virtually from 63 countries. The conference was organized by IPAP and hosted by the Vaccine and Infectious Disease Forum of Sri Lanka, Sri Lanka College of Pediatricians, Sri Lanka College of Microbiologists and College of General Practitioners of Sri Lanka, with the support of the Ministry of Health, Sri Lanka. The 9th ASVAC is scheduled to be held in Davao City, Philippines in late 2023.